Források és módszerek a Debreceni Református Kollégium diáknévsorainak feldolgozásához - Szabadi, István (Gerundium, 2015)
SOURCES AND METHODS FOR PROCESSING STUDENT LISTS OF THE DEBRECEN REFORMIST COLLEGE. In commemoration of the 475th anniversary of the existence of the Debrecen Reformist College a long expected, two volume resource guide was published in 2013 under the title „History sources of the institution int he archive of the Debrecen Reformist College.” It contains student lists between 1588 and 1850 cataloguing 20 000 registrations. his essay summarizes the history of this research and lists the sources used in the process.